Normal solid gastric emptying values measured by scintigraphy using asian-style meal: A multicenter study in healthy volunteers - Pataramon Vasavid (2018)
Background/Aims: To report gastric emptying scintigraphy, normal values should be established for a specific protocol. The aim of this study was to provide normal gastric emptying values and determine factors affecting gastric emptying using Asian rice-based meal in healthy volunteers. Methods: One hundred and ninety-two healthy volunteers were included at 7 tertiary care centers across Thailand. Gastric emptying scintigraphy was acquired in 45 degree left anterior oblique view immediately after ingestion of a 267 kcal steamed-rice with technetium-99m labeled-microwaved egg meal with 100 mL water for up to 4 hours. Results: One hundred and eighty-nine volunteers (99 females, age 43 ± 14 years) completed the study. The medians (5-95th percentiles) of lag time, gastric emptying half time (GE T1/2) and percent gastric retentions at 2 and 4 hours for all volunteers were 18.6 (0.5-39.1) minutes, 68.7 (45.1-107.8) minutes, 16.3% (2.7-49.8%) and 1.1% (0.2-8.8%), respectively. Female volunteers had significantly slower gastric emptying compared to male (GE T1/2, 74 [48-115] minutes vs. 63 (41-96) minutes; P < 0.05). Female volunteers who were in luteal phase of menstrual cycle had significantly slower gastric emptying compared to those in follicular phase or menopausal status (GE T1/2, 85 [66-102] mintes vs. 69 [50-120] minutes or 72 [47-109] minutes, P < 0.05). All of smoking volunteers were male. Smoker male volunteers had significantly faster gastric emptying compared to non-smoker males (GE T1/2, 56 [44-80] minutes vs. 67 [44-100] minutes, P < 0.05). Age, body mass index and alcohol consumption habits did not affect gastric emptying values. Conclusions: A steamed-rice with microwaved egg meal was well tolerated by healthy volunteers. Gender, menstrual status and smoking status were found to affect solid gastric emptying. © 2014 The Korean Society of Neurogastroenterology and Motility.